To simplify the expression \( \frac{2}{5}\left(\frac{3}{4}p + \frac{5}{6}w\right) + \frac{1}{5}\left(\frac{1}{2}p - 6\frac{2}{3}w\right) \), we will follow these steps:
- Distribute the terms inside the parentheses.
- Combine like terms.
Step 1: Distribute the terms
First term: \[ \frac{2}{5}\left(\frac{3}{4}p + \frac{5}{6}w\right) = \frac{2}{5}\cdot\frac{3}{4}p + \frac{2}{5}\cdot\frac{5}{6}w \]
Calculating \( \frac{2}{5} \cdot \frac{3}{4} \): \[ \frac{2 \cdot 3}{5 \cdot 4} = \frac{6}{20} = \frac{3}{10} \] So, the first term becomes: \[ \frac{3}{10}p \]
Calculating \( \frac{2}{5} \cdot \frac{5}{6} \): \[ \frac{2 \cdot 5}{5 \cdot 6} = \frac{10}{30} = \frac{1}{3} \] So, the first term for \( w \) becomes: \[ \frac{1}{3}w \]
Combining these, we have: \[ \frac{2}{5}\left(\frac{3}{4}p + \frac{5}{6}w\right) = \frac{3}{10}p + \frac{1}{3}w \]
Second term: \[ \frac{1}{5}\left(\frac{1}{2}p - 6\frac{2}{3}w\right) = \frac{1}{5} \cdot \frac{1}{2}p - \frac{1}{5} \cdot 6\frac{2}{3}w \]
Calculating \( \frac{1}{5} \cdot \frac{1}{2} \): \[ \frac{1}{10}p \]
Calculating \( 6\frac{2}{3} \): \[ 6\frac{2}{3} = 6 + \frac{2}{3} = \frac{18}{3} + \frac{2}{3} = \frac{20}{3} \] Now calculate \( \frac{1}{5} \cdot \frac{20}{3} \): \[ \frac{20}{15} = \frac{4}{3} \] So, the second term becomes: \[ -\frac{4}{3}w \]
Step 2: Combine like terms
Now we combine both parts: \[ \left(\frac{3}{10}p + \frac{1}{3}w\right) + \left(\frac{1}{10}p - \frac{4}{3}w\right) \]
Combining the \( p \) terms: \[ \frac{3}{10}p + \frac{1}{10}p = \frac{4}{10}p = \frac{2}{5}p \]
Combining the \( w \) terms: \[ \frac{1}{3}w - \frac{4}{3}w = -\frac{3}{3}w = -w \]
Final Answer:
Putting it all together: \[ \frac{2}{5}p - w \]
Thus, the simplified expression is: \[ \boxed{\frac{2}{5}p - w} \]